(Re)Viewing Reviews: Effects of Emotionality and Valence on Credibility Perceptions in Online Consumer Reviews. Issue 3 (3rd July 2017) - Vendemia, Megan A.
Abstract : This study examines credibility perceptions in online consumer reviews. Specifically, this work investigates the effects of review emotionality (high vs. low), review valence (positive vs. negative), and individuals' need for affect on source credibility and information credibility. In an online experiment, U.S. adults ( N  = 327) viewed a product review from Amazon.com varied across four experimental conditions. Results indicate that high-emotionality reviews are perceived as lower in source and information credibility compared to low-emotionality reviews. A moderated mediation model was tested with the source credibility dimensions as possible mediators of information credibility and need for affect as a moderator for the effects of review emotionality. The effects of emotionality on information credibility were significantly mediated by source trustworthiness, and this mediation was moderated by participants' need for affect, with the credibility-hampering effects of emotionality found only among participants with low and moderate levels of need for affect.